Comparative Study of the Effect of Dexmedetomidine Vs. Fentanyl on Haemodynamic Response in Patients Undergoing Elective Laparoscopic Surgery - Jayshree P Vaswani (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Dexmedetomidine and fentanyl, both have sedative and analgesic effects. They are often used as adjunct during anaesthesia to attenuate pressor response during tracheal intubation. Limited study has been done comparing the effect of both drugs on haemodynamic response in patients undergoing laparoscopic surgery. Aim: The study was designed to compare the effect of dexmedetomidine Vs fentanyl on haemodynamic response to tracheal intubation, following pneumoperitoneum and intraoperative period in patients undergoing laparoscopic surgery. Materials and Methods: Sixty patients of age group 18-60 years of either sex, classified as American Society of Anaesthesiologist (ASA) Grade I and II undergoing elective laparoscopy surgery were randomly allocated to one of the two groups (Group-D) and (Group F) of 30 each. Group D received dexmedetomidine and Group F received fentanyl. Patients received intravenous 0.5 µg/kg of the study drug as loading dose over 10 minutes prior to intubation followed by 0.2-0.7 µg/kg/hr as infusion till surgery was over. In operating room parameters like Heart Rate (HR), Respiratory Rate (RR), Systolic Blood Pressure (SBP), Mean Arterial Pressure (MAP), SpO2 , EtCO2 were recorded 10 minutes after infusion of drug i.e., dexmedetomidine or fentanyl. The said parameters were again recorded after injection of induction drugs, after intubation, five minutes after intubation, just after pneumoperitoneum, and 5,10,15,30,45 and 60 minutes after pneumoperitoneum, five minutes after release of pneumoperitoneum, five and 10 minutes after extubation. Results: Dexmedetomidine significantly attenuates stress response at intubation with lesser increase in HR (5% Vs 18%), SBP (9% Vs 19%) and DBP (3% Vs 15%), MAP (2% Vs 15%) as compared to fentanyl (p<0.05). Throughout intraoperative period of pneumoperitoneum Group D showed significant fall in HR, SBP, DBP, MAP from baseline value at all points of time intervals whereas it remained constantly high above baseline value in Group F (p-value <0.05). Conclusion: Dexmedetomidine when compared to fentanyl causes greater attenuation of stress response to tracheal intubation, following pneumoperitoneum and in intraoperative period resulting in greater reduction of HR, SBP, DBP, MAP than that of fentanyl, thus causing better haemodynamic stability in patients undergoing elective laparoscopic surgery.